Does Seasonality and Stochastic Cycles Affect Output Growth in Nigeria? Lessons for Development Planning - Ogujiuba, Kanayo; Abraham, Terfa W; Stiegler, Nancy (Journal of Economics and Behavioral Studies, 2016)
This paper examines the seasonality and stochastic cycle associated with GDP growth in Nigeria using two measures of filter. Our findings include, that the Christiano & Fitzgerald (2003) filter removed low-periodicity stochastic cycles associated with output growth in Nigeria compared to the Hodrick Prescott filter. The smoothed GDP trend further revealed that growth in Nigeria was higher but unstable in periods of development planning than in periods without development plans. This suggests that development planning in Nigeria was not accompanied by judicious mix of fiscal and monetary policy in the 1980s/1990s. Likewise, effort to achieve sustainable growth and development, since the return to democracy in 1999, has not been accompanied by effective planning. To achieve inclusive development therefore, there is the need to return to development planning in order to address the destruction meted by insurgents in the North east and the lack of inclusiveness in Nigeria’s growth observed in recent times.